Tort in Land Grabbing - Meliyani Sidiqah (Universitas Muhammadiyah Palu, 2020)
Land grabbing is taking or seizing other people's land for personal gain and causing losses to landowners. The lawsuit in Verdict Number 19/Pdt/G/2011/PN. Krw. Originated from the actions of the father of Defendants, who sold the Plaintiffs' land without any rights, as well as the activities of the Co-Defendants, who bought land from the father of Defendants without any rights. This action was very detrimental to the Plaintiffs. This article aims to analyze the activities of the Defendants and the Co-Defendants in tort and the consideration taken by the Panel of Judges in rejecting and or granting a tort lawsuit. This article results from normative juridical research using statutory and case approaches. The data used are secondary data, including primary legal materials, secondary legal materials, and tertiary legal materials, collected by literature study and then analyzed using qualitative analysis methods. Based on the research results, the actions committed by the Defendants and Co-Defendants were a tort, and the Panel of Judges partially granted the Plaintiff's claim.